2020
DOI: 10.1016/j.ijom.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw in patients with inflammatory bowel disease treated with tumour necrosis factor alpha inhibitors

Abstract: Previous reports have suggested a possible association between tumour necrosis factor alpha (TNF-a) inhibitors, used in the treatment of immune-mediated inflammatory diseases, and medication-related osteonecrosis of the jaw (MRONJ). However, a comprehensive assessment of the frequency and severity of MRONJ caused by these agents is lacking. The aim of this cohort study was to investigate the occurrence of MRONJ in a population of patients with inflammatory bowel disease (IBD) treated with TNF-a inhibitors at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Fang's study has shown the effects of TNFα on proliferation, angiogenesis, and osteogenesis, and osteogenesis of rat bone mesenchymal stem cells (rMSCs) 38 . TNF-α plays as a mediator of bone destruction by stimulating osteoclastogenesis [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Fang's study has shown the effects of TNFα on proliferation, angiogenesis, and osteogenesis, and osteogenesis of rat bone mesenchymal stem cells (rMSCs) 38 . TNF-α plays as a mediator of bone destruction by stimulating osteoclastogenesis [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in three patients with a definite diagnosis of MRONJ, without concomitant treatment with bisphosphonates. This study identified and described anti-TNF-α-related MRONJ occurring in a large cohort of patients with inflammatory bowel disease [18]. In the current case, mandibular osteonecrosis developed after years of infliximab treatment, without bisphosphonate administration, but in co-therapy with corticosteroids.…”
Section: Case Reportmentioning
confidence: 72%
“…However, the role of this anti-TNF-α antibody therapy to the manifestation of osteonecrosis in this case was not clearly established due to the concomitant administration of bisphosphonates. Brijs et al (2019) investigated the occurrence of MRONJ in a population of patients with inflammatory bowel disease treated with TNF-a inhibitors at a tertiary care medical center over a 24-year period [18]. These patients were cross-matched with all patients diagnosed with MRONJ.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations